[OP.8A.03] LONG-TERM EFFECTS OF LEISURE TIME PHYSICAL ACTIVITY ON SMALL ARTERY ELASTICITY INDEX: THE SKARABORG PROJECT. (September 2016) - Daka, B.; Allison, M.; Larsson, C.A.; Hellgren, M.I.; Råstam, L.; Lindblad, U.L.F.
Abstract : Objective: Small artery elasticity index (SAEI) have been associated with incident hypertension and incident cardiovascular disease (CVD), independent of relevant risk factors. The aim of this study was to investigate the association between the intensity of LTPA and SAEI at baseline and at follow-up in a prospective design. Design and method: In this longitudinal observational study, a representative cohort (2816 individuals, ∼50% male) in southwestern Sweden, aged 35–75 at baseline was followed for 9.7 ± 1.4 years. Of these, a representative subpopulation of 1062 individuals (534 women and 528 men) had complete information at baseline and follow-up. SAEI, assessed using HDI/Pulse wave CR-2000 (Eagan, MN), and anthropometric were collected at baseline and at follow up. The change in mean SAEI between baseline and follow-up was calculated as (SAEI1-SAEI2)/((SAEI1 + SAEI2)/2). Diabetes was assessed using OGTT and physician diagnosis based on WHO 1999, while hypertension was defined based on JNC7. Information regarding lifestyle was collected using validated questionnaires. The initial 4 levels of self-reported LTPA were dichotomized into two categories: sedentary (level 1–2) and physically active (level 3–4). General linear models with adjustments for possible confounders were used to assess differences between categories. Results: At baseline (after adjustment for age, sex, systolic blood pressure, use of blood pressure lowering drugs, diabetes, waist hip ratio, HOMA-IR and smoking), the sedentary group had significantly lower SAEI than the physically active group (7.85 vs 8.33 ml/mmHg, p < 0.01). Using the same model, similar differences were observed at the follow-up visit (sedentary = 6.56 vs. active = 7.07, p < 0.01). Although a significant decrease in SAEI was observed in the whole group over the follow-up period (from 8.0 to 6.7 ml/mmHg, p < 0.001), the change in SAEI was similar in the two LTPA groups (sedentary = 0.19 vs active = 0.18, p = 0.75). Conclusions: In this cohort, the level of physical activity at baseline did not influence the decrease in SAEI. However, moderate to intensive LTPA was associated with higher SAEI and this association persisted during follow up. These results suggest a long-term beneficial effect of LTPA on the vascular function.